2020
DOI: 10.1007/s40858-020-00386-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding psyllid transmission of Candidatus Liberibacter as a basis for managing huanglongbing

Abstract: Citrus huanglongbing (HLB) represents a major threat to citriculture due to its rapid spread, difficulty of control, severe yield losses, and substantial increases in production costs in HLB-affected orchards. Successful management depends on detailed knowledge of the epidemiology of this disease, which is associated with phloem-limited bacteria of the genus Candidatus Liberibacter that are transmitted by phloem sap-feeding insects known as psyllids (Hemiptera: Psylloidea). Candidatus L. asiaticus (CLas) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 111 publications
(160 reference statements)
3
21
0
Order By: Relevance
“…Although we did not explicitly test color morph influence on CLas transmission, the feeding behavior data presented here can be extrapolated to consider color morph effects based on known associations between vector feeding and the acquisition and inoculation of phloem restricted pathogens (Ebert 2019: Carmo-Souza et al 2020. Since CLas inoculation is related to the frequency and duration of phloem salivation events (Wu et al 2016;Carmo-Sousa et al 2020), the lack of differences detected for the E1 parameter support the hypothesis of no correlation between color morphology and CLas inoculation. Therefore, it is likely that if there are differences in CLas transmission between color morphs, the differences could be attributed to variation in the retention or replication of the bacteria in key organs, such as the salivary glands.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although we did not explicitly test color morph influence on CLas transmission, the feeding behavior data presented here can be extrapolated to consider color morph effects based on known associations between vector feeding and the acquisition and inoculation of phloem restricted pathogens (Ebert 2019: Carmo-Souza et al 2020. Since CLas inoculation is related to the frequency and duration of phloem salivation events (Wu et al 2016;Carmo-Sousa et al 2020), the lack of differences detected for the E1 parameter support the hypothesis of no correlation between color morphology and CLas inoculation. Therefore, it is likely that if there are differences in CLas transmission between color morphs, the differences could be attributed to variation in the retention or replication of the bacteria in key organs, such as the salivary glands.…”
Section: Discussionmentioning
confidence: 67%
“…Phloem access and exploitation is also essential for CLas transmission. Therefore, understanding how color polyphenism influences adult ACP interactions with phloem tissues will provide information about how ACP physiology affects the probability of CLas inoculation (Bonani et al 2010;Luo et al 2015;Wu et al 2016;Killiny et al 2017;Carmo-Sousa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was shown that the expression levels of CaLasSDE115 were significantly higher in psyllids compared with those in plants. In the same way in which Bartonella species enter mammalian erythrocytes ( Deng et al, 2018 ), Ca Las cells enter a psyllid’s body by crossing the gut epithelium before subsequently moving to other internal organs and tissues ( Carmo-Sousa et al, 2020 ). Thus, it is suggested that CaLasSDE115 could also be involved in Ca Las’s entry and intracellular movement in the Asian citrus psyllid.…”
Section: Discussionmentioning
confidence: 99%
“…Adult psyllids are responsible for the spreading of CLas, whereas, D. citri nymphs are known for greater acquisition efficiency, as well as faster CLas replication (George 2018;Ammar et al 2016;Gottwald 2010). The voluntary and involuntary movement of adult psyllids is associated with wind speed and direction (Carmo-Sousa et al 2020). The mean annual wind speed in MG ranged between 6.19 to 12.8 km/h.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of HLB throughout Brazilian states can be attributed to the psyllid vectors' capability of short (plant-to-plant and within orchard; 5-320 m) and long-distance (between orchard; ~2.5 km) movement via passive and active strategies, i.e., windassisted dispersal and consecutive short flights, respectively (Carmo-Sousa et al 2020;Antolinez et al 2021). Additionally, the use of infected propagative material through grafting has also been demonstrated to transmit HLB and can thus contribute to the dissemination of the pathogen (van Vuuren & da Graça, 1993).…”
Section: Introductionmentioning
confidence: 99%